Constraint Review and Implementation of audits on technology-based Startup Companies in Indonesia - Erwin Setyadi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
The future of digital and internet technology-based companies is very prospective. But some obstacles also arise because not all startups have angel investors who are willing to inject large initial capital for initial operations. Accounting standards used to assess startup market capitalization are quite difficult to apply because what is assessed is not real assets but rather the potential market share of users of their technology products or applications, which tends to be volatile and uncertain. Another obstacle in the audit process is that most data processing activities take place using (computer) programs, which physically cannot be seen. This paper discusses the obstacles faced by startup companies and the implementation of their audits.